Care, Loss and the End of Life
1 online resource.
Keywords: This inter- and multi-disciplinary volume examines various experiences of loss, whether we encounter it in the form of lost loved ones, lost relationships, lost opportunities or the loss of capabilities as we age. Loss is something we can experience personally, as part of a family, and as part of a community whose collective experiences of loss occasions more public displays of commemoration. We are constantly challenged to find ways of coping and surviving in the face of different types of loss. Due in part to the complexities of the concept itself and the resistance many individuals feel toward discussing painful subjects, it is often difficult to engage in the sort of robust, inter-disciplinary dialogue that is needed to explore fully the links between living, suffering, dying, and surviving loss. Thus, this volume is profoundly interdisciplinary, as it explores how loss can be expressed through cognitive, affective, somatic, behavioral/interpersonal, and spiritual grief responses.